Fungal extracellular phosphatases: their role in P cycling under different pH and P sources availability - Della Mónica, Ivana Florencia (2018)
Aims: The aim of this work is to analyse the effect of pH, fungal identity and P chemical nature on microbial development and phosphatase release, discussing solubilization and mineralization processes in P cycling. Methods and Results: P solubilizing fungi (Talaromyces flavus, T. helicus L, T. helicus N, T. diversus and Penicillium purpurogenum) were grown under three pH conditions (6, 6·5 and 8·5) and with different inorganic (calcium, iron, aluminium and rock) and organic (lecithin and phytate) P sources. P solubilization, mineralization, growth and phosphatase production were recorded. Acid and neutral environments maximized fungal development and P recycling. P chemical nature changed the phosphatases release pattern depending on the fungal identity. Acid phosphatase activity was higher than alkaline phosphatases, regardless of pH or sample times. Alkaline phosphatases were affected by a combination of those factors. Conclusions: P chemical nature and pH modify fungal growth, P mineralization and solubilization processes. The underlying fungal identity-dependent metabolism governs the capacity and efficiency of P solubilization and mineralization. P solubilization and mineralization processes are interrelated and simultaneously present in soil fungi. Significance and Impact of the study: This study constitutes a reference work to improve the selection of fungal bioinoculants in different environmental conditions, highlighting their role in P cycling.